Enhancing Sociolinguistic Competence for Journalism Students (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The formation and development of socio-cultural competence are crucial components of effective foreign language education. Sociolinguistic competence encompasses various structures, mechanisms, and strategies employed by speakers in different communicative contexts (Bayley & Regan, 2004). This article examines the key elements of sociolinguistic competence, emphasizing its relevance in higher education and the challenges associated with its acquisition. It also explores how native speakers contribute to shaping learners' social and linguistic competencies during the educational process. The study further highlights the necessity of integrating models of interaction, discourse practices, and social dialect selection into language teaching. Given the evolving landscape of language education, a synthesis of teaching methods and innovative pedagogical approaches is essential to develop socio-cultural competence effectively. The research presents an experimental study conducted in European institutions of higher education, analyzing the relationship between students' success and the activation of social competence in foreign language acquisition. The findings suggest that interactive learning methods and digital technologies play a significant role in enhancing socio-cultural competence, ultimately influencing students' professional development.